Fast-Discharging Apparatus 0 - 400 A / 2 - 4.2 V for Testing of Lithium Cells. (3rd December 2015) - Martis, Jan; Vorel, Pavel; Prochazka, Petr; Cipin, Radoslav; Pazdera, Ivo
Abstract : This paper describes an apparatus developed for testing fast-discharging processes of lithium cells. The device is equipped with a current control loop which enables to set the discharging current manually in a range from 0 to ca. 400 A. A constant current discharging independent on the load voltage is ensured this way. In principle the load is created with a set of power MOSFETs operating in linear regime. Further, some passive power resistors are used to decrease the MOSFET power loss and to equalize the currents of individual MOSFETs. An analog control circuit is used. The developed device was used for testing the LiFePO4 cell of type AS-71J0280-2AA0-110 (3.2 V / 200 Ah). Its discharging characteristics with various constant discharging currents were measured and compared with the datasheet values. Also its charging characteristics (CC/CV method) were measured.